Biotechnological Approaches for Genetic Improvement of Crops - Tinee Adlak; Sushma Tiwari; Madhurjit Singh Rathore; Niraj Tripathi; Prakash Narayan Tiwari; M. K. Tripathi (Cutting Edge Research in Biology Vol. 7, 2023)
Biotechnological approaches are being used widely in modern plant breeding for genetic improvement of crops for targeted traits and yield. The conventional breeding methods are mostly based on hybridization and selection of advance breeding lines. Advance biotechnological methods are rapidly being employed for achieving improved varieties in less span of time with desirable traits. These methods include plant tissue culture, molecular breeding, and transgenic methods. Plant tissue culture is helpful in getting somaclonal variants, embryo rescue, and for mass propagation of plants through micropropagation, while molecular breeding is being applied for marker assisted selection, varietal characterization, foreground and background selection and transgenics approaches are being used to transfer gene from different background in genome of crop plants. High throughput genotyping, next generation sequencing and genome editing are some of the recent biotechnological tools being applied for successful crop improvement programme. Current book chapter focused on overview of some of the important biotechnological tools being applied for crop improvement.